Lesion characteristics of acute myocardial infarction: an investigation with intravascular ultrasound. Issue 4 (1st April 2001) - Fukuda, D; Kawarabayashi, T; Tanaka, A; Nishibori, Y; Taguchi, H; Nishida, Y; Shimada, K; Yoshikawa, J
Abstract : OBJECTIVE: To use intravascular ultrasound (IVUS) to compare plaque morphology in acute myocardial infarction and stable angina pectoris. DESIGN: Retrospective study. SETTING: Primary care hospital. PATIENTS: 59 consecutive cases of acute myocardial infarction and 50 consecutive cases of stable angina pectoris. METHODS: IVUS was used before coronary intervention. MAIN OUTCOME MEASURES: Plaque morphology (incidence of eccentric plaque, subtle dissections, low echoic thrombus, calcification, echolucent areas, and bright speckled echo material), assessed visually using IVUS. RESULTS: There were no significant differences in plaque eccentricity or calcification between the two groups, but low echoic thrombus (acute myocardial infarction 15% v stable angina pectoris 0%), subtle dissections (37% v 4%), echolucent areas (31% v 0%), and bright speckled echo material (90% v 0%) were more common in the infarction group than in the stable angina group (p < 0.001 for all). There was a longer time between the onset of symptoms and the IVUS examination in patients with low echoic thrombus than in those without (p < 0.03). CONCLUSIONS: Low echoic thrombus, subtle dissections, echolucent areas, and bright speckled echo material are morphological characteristics associated with plaque at the time of acute myocardial infarction. These findings correspond pathologically to ruptured plaque.